Endoscopic ultrasound–guided luminal remodeling as a novel technique to restore gastroduodenal continuity. (September 2020) - El Bacha, Hicham; Jung, Carlo; Brieau, Bertrand; Bordacahar, Benoit; Leblanc, Sarah; Barret, Maximillien; de Chaumont, Arthus; Dousset, Bertand; Prat, Frederic
Pyloric exclusion is a method of treatment for duodenal injury. Surgery is usually needed to restore digestive continuity in due time, yet a new surgical procedure can be challenging due to fibrotic adhesion development. We present here a retrospective case series of three patients with pyloric exclusion who underwent endoscopic ultrasound–guided duodenal repermeabilization using metallic stents. All procedures were successful with no complication and allowed regular feeding. This case series shows that endoscopic ultrasound–guided recanalization is a feasible and safe procedure.